2015
DOI: 10.1111/lasr.12167
|View full text |Cite
|
Sign up to set email alerts
|

Faith in the Court: Religious Out-Groups and the Perceived Legitimacy of Judicial Decisions

Abstract: The question of whether judges’ personal characteristics and values bias their decision making has long been debated, yet far less attention has been given to how personal characteristics affect public perceptions of bias in their decision making. Even genuinely objective judges may be perceived as procedurally biased by the public. We hypothesize that membership in a religious out‐group will elicit stronger public perceptions of biased decision making. Using a survey experiment that varies a judge's religious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
1
2
0
1
Order By: Relevance
“…Of the 110 MTurkers, seven participants' data were excluded for missing over five answers, missing attention checks, or for already completing the first survey.Previous research has demonstrated that MTurk worker behavior and laboratory participant behavior is equivalent(Horton, Rand, & Zeckhauser, 2011). However, the pilot study found results consistent with previous research on the demographic composition of MTurk workers, in which over 31% of the participants in the pilot study identified as nonreligious Audette and Weaver (2015). found similar results using MTurk with over 40% of their participants reporting that they have no religion and over 20% identifying as Atheist.…”
supporting
confidence: 86%
“…Of the 110 MTurkers, seven participants' data were excluded for missing over five answers, missing attention checks, or for already completing the first survey.Previous research has demonstrated that MTurk worker behavior and laboratory participant behavior is equivalent(Horton, Rand, & Zeckhauser, 2011). However, the pilot study found results consistent with previous research on the demographic composition of MTurk workers, in which over 31% of the participants in the pilot study identified as nonreligious Audette and Weaver (2015). found similar results using MTurk with over 40% of their participants reporting that they have no religion and over 20% identifying as Atheist.…”
supporting
confidence: 86%
“…Чтобы правительство было легитимным, решения должны быть справедливыми и каждый должен иметь возможность в какой-то момент оказаться в выигрыше (Buhlmann & Kunz, 2011). Судебные органы должны обладать институциональной легитимностью, которая заключается в том, что общественность будет поддерживать их решения и полномочия (Audette & Weaver, 2015) независимо от степени удовлетворенности решениями (Buhlmann & Kunz, 2011). Без легитимности суды не обладают достаточной властью, чтобы в случае необходимости принимать решения вопреки общественному мнению.…”
Section: легитимностьunclassified
“…For governments to appear legitimate, decisions must be fair, and everyone must have an opportunity to benefit at some point (Bühlmann & Kunz, 2011). The judiciary needs to have institutional legitimacy, which is the concept that the public will support their decisions and authority (Audette & Weaver, 2015) regardless of the satisfaction level of the decisions (Bühlmann & Kunz, 2011). Without legitimacy, the courts do not have enough power to rule against public opinion when necessary.…”
Section: Legitimacymentioning
confidence: 99%